Validation of the BDI-II in South Africa - Makhubela, Malose Silas (My University, 2015)
The present study investigated whether the Beck Depression Inventory-II (BDI-II) measures the same construct in exactly the same way across the groups of interest and time in South Africa. The degree to which items or subtests of the BDI-II have equal meaning across qualitatively distinct groups of examinees (e.g., culture and gender) was explored. Measurement Invariance (MI) of the BDI-II across race (blacks and whites), gender and time (two weeks lag) was examined in a sample of university students, from two universities located in diverse geographical regions of South Africa (N = 919). Confirmatory factor analysis (CFA) was used to test the fit of the hypothesized three-factor model established through exploratory factor analysis (EFA), and the results from these analyses indicated that the BDI-II was most adequately represented by a three lower-order factor structure (appropriately named Negative attitude, Performance difficulty and Somatic complaints). Results based on multigroup confirmatory factor analysis (MCFA) (i.e., means and covariance structures [MACS]) indicated that there was factorial invariance for this three lowerorder factor structure across groups and time, suggesting that the BDI-II provides an assessment of severity of depressive symptoms that is equivalent across race, gender and time in university students. Results indicated that MI was established at the level of configural, metric and scalar invariance for race, gender and across time. However, there was some evidence of differential item functioning (DIF) and differential additive response style (ARS) across race, with two noninvariant intercepts (items 5 and 14) and three item intercepts (items 11, 14 and 18) across gender being identified. Additionally, results of latent mean differences were presented to explain group differences. The study concluded with recommendations for future studies.
Thesis (Ph. D. (Psychology)) -- University of Limpopo, 2015
Keywords: Depression; 362.25; Beck Depression Inventory; Depression, Mental -- Testing; College students